12 Role of an Integrated Arrhythmia Service: From Emergency Room to Radio Frequency Ablation. (31st May 2014) - El sayed, Hossam; Muhammad Rashid, Val; Douglas, Homeyra; Miro, Firas; Hung, John
Abstract : Background: Atrial fibrillation (AF) is the most common arrhythmias managed by emergency physician. In 2005, a chapter setting out best practice for arrhythmia care and sudden cardiac death (SCD) was added to the National Service Framework for Coronary Heart Disease. This highlighted the need for early diagnosis and expert patient support. Methods: A nurse led arrhythmia service was set up in 2011. The aim of this service was to develop and improve care pathways, avoid hospital admissions and reduce the length of stay (LOS) as well as providing continuity and support for patients diagnosed with an arrhythmia. Malignant ventricular arrhythmias were excluded. The nurses also managed a caseload of cardio version patients, undertaking pre and post procedure clinics, patient assessment and titration of anticoagulation therapy prior to performing the direct current cardio version (DCCV) itself. The service received referrals for the monitoring of anti-arrhythmic drugs and family screening for SCD. All patients are assessed by the nurse in the emergency room(ER). Depending on the severity of symptoms, the patient would either be discharged home or admitted. All patients would be seen within 24–48 hrs of being discharged. We also compared admission rates and LOS before and after the establishment of the service. All treatment regimes were as per the standardised AF management pathways. Results: A total of 1169 patients were seen in arrhythmia service from 2011–2013.Eighty seven percent (1020 patients) were referred from the ER (Table 1 ). The most common referrals were for atrial fibrillation (77%), atrial Flutter (12%) and palpitations (10%). Thirty three percent of patients with acute AF were discharged from ER on the same day (n = 343). Of those who required admission (n = 677), 36% were discharged within the first 48 h (n = 246). The average LOS for AF was significantly improved compared to the pre Arrhythmia service era (2.6vs 7.3 days). The majority of patients with acute presentation were considered for a rate control strategy and one third of patients were referred for DCCV (n = 249). Majority of patients were discharged back to GP after treatment optimisation (87%), the rest were referred to cardiologist for further management (40% were referred for consideration of radiofrequency ablation, n = 93). There were no reported deaths or major adverse cardiac events (MACE) and the readmission rate was 1%. Conclusion: The presence of an integrated Arrhythmia Service in the Emergency Room reduces hospital admissions as well as improving access and delivery of patient care. Nurse-led rapid access clinics provides close monitoring of the patients in an ambulatory setting resulting in less admissions and shorter LOS. A pre and post procedure clinics have led to freeing up valuable clinician's time.